Lecythidaceae endémicas del Perú - León, Blanca (2006)
Lecythidaceae are represented in Peru by eight genera and 20 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all of them trees. Here we recognize two endemic species in two genera. These endemic taxa grow in the Humid Lowland Amazonian Forest region, between 100 and 270 m elevation. One endemic species of Lecythidaceae has been registered in the Peruvian protected areas system.